Optimal experimental design for cytogenetic dose–response calibration curves. (2nd July 2020) - Higueras, Manuel; Howes, Adam; López-Fidalgo, Jesús
Abstract: Purpose: To introduce optimal experimental design techniques in the cytogenetic biological dosimetry practice. This includes the development of a new optimality criterion for the calibration of radiation doses. Materials and methods: The most typical optimal design criterion and the one developed in this research are introduced and applied in an example from the literature. In another example from the literature, a simulation study has been performed to compare the standard error of the dose estimation using different experimental designs. An RStudio project and a GitHub project have been developed to reproduce these results. Results: In the paper, it is observed that the application of optimal experimental design techniques can reduce the standard error of biodosimetric dose estimations. Conclusions: Optimal experimental design techniques jointly with practitioners' requirements may be applied. This practice would not involve an additional laboratory work.